2021
DOI: 10.1101/2021.08.28.458034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local mechanical stimuli shape tissue growth in vertebrate joint morphogenesis

Abstract: The correct formation of synovial joints is essential for proper motion throughout life. Movement-induced forces are critical to creating correctly shaped joints, but it is unclear how cells sense and respond to these mechanical cues. To determine how mechanical stimuli drive joint morphogenesis, we combined experiments on regenerating axolotl forelimbs with a poroelastic model of bone rudiment growth. Animals either regrew forelimbs normally (control) or were injected with a TRPV4 agonist to impair chondrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 81 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…Whereas atomic force microscopy-based indentation measurements, the current gold standard in mechanobiology [49], have been more extensively used in the field [5052], albeit with the limitation of measuring processed tissues from ex vivo explants. In urodeles, the only studies on tissue mechanics were performed either in vitro , demonstrating that wound closure of skin explants strongly relies on the substrate biomechanical properties [53], or in silico , predicting that movement-induced interstitial pressure promotes tissue growth during joint morphogenesis [54]. Hence, further in vivo studies need to be carried out to better understand the influence of mechanics on regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas atomic force microscopy-based indentation measurements, the current gold standard in mechanobiology [49], have been more extensively used in the field [5052], albeit with the limitation of measuring processed tissues from ex vivo explants. In urodeles, the only studies on tissue mechanics were performed either in vitro , demonstrating that wound closure of skin explants strongly relies on the substrate biomechanical properties [53], or in silico , predicting that movement-induced interstitial pressure promotes tissue growth during joint morphogenesis [54]. Hence, further in vivo studies need to be carried out to better understand the influence of mechanics on regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Comellas et al identified differences in joint morphology between control and TRPV4-blocked regenerating limbs in axolotls, emphasizing the need for a comprehensive 3D analysis of the regenerated limb for a more nuanced understanding of morphological distinctions 11 . To enhance our understanding, future studies could incorporate tracking proliferating cells, offering a more comprehensive insight into the effects of TRPV4 impairment on limb regeneration 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical loading experienced by growing musculoskeletal tissues generates stimuli that embryonic cells perceive and respond to, translating mechanical signals into molecular responses 5 . Disruption of these mechanical signals during development has been shown to result in significant alterations to joint morphology, tissue composition, and the manifestation of pathology [11][12][13] Methods: This study focused on estimating the viscoelastic material properties during three regeneration stages of axolotl (Ambystoma mexicanum) forelimbs: 27 days post-amputation or 27 DPA (mid-late bud), 41 DPA (palette stage), and fully-grown time points. Material parameters were derived through a stress-relaxation indentation test followed by a two-term Prony series viscoelastic inverse finite element analysis.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations